Legal Protection for Female Victims of Electronic-based Sexual Violence (EBSV): A Legal System Theory Perspective - Nur Alfy Syahriana; Erfaniah Zuhriah; Ahmad Wahidi (Sawwa: Jurnal Studi Gender)
Since 2017-2021, case of electronic-based sexual violence (EBSV) reported to service institution continues to increase, and a majority of the victims are women. This research aims to describe the EBSV case data, explain legal protection efforts given to the victims, then analyze it using the legal system theory. The type of research used is juridical-empirical with locus research at Women Crisis Centre (WCC) Dian Mutiara. The research results show that on month January 2020 - September 2022, there were 42 cases handled by WCC Dian Mutiara. Then the legal protection for victims is carried out through preventive and repressive efforts. In terms of legal structure, the facilities and infrastructure for handling KSBE cases at WCC Dian Mutiara and the police are not yet fully available. At WCC Dian Mutiara, this can be seen from the lack of human resources (assistants) and the unstable finances of the institution. Meanwhile, in the police, it can be seen from the victim's complaint at the time of confiscation of evidence in the form of a handphone which is usually used for daily activities by the victim. Then the analysis of the legal substance shows that the rules regarding EBSV already exist in the Law on Electronic Transactions (UU ITE) and the Pornography Law, but more comprehensive rules are contained in the Law on Crimes against Sexual Violence (RUU TPKS). Finally, an analysis of legal culture shows that public oversight of the performance of law enforcers, especially the police, is increasing. However, sometimes the community's understanding of a case is still partial, making it easy to intervene. Meanwhile, the legal culture of law enforcement officials can be seen from the lack of optimal cases in the process of resolving cases, coupled with the occasional attitude of the police, not on the side of the victims.